A multidimensional comparison of the benefit degrees for patients between ileostomy and colostomy - Wang, Yuhang; Cheng, Lei; Li, Weichao; Gao, Zhaowei; Miao, Jiayuan; Zhang, Chunlei; Zhu, Zhiqiang; Zhao, Feng; Yi, Jing; Liu, Chunyuan (Frontiers in Medicine, 2025)
IntroductionEnterostomy is widely used in the treatment of various diseases, especially in the treatment of colorectal malignant tumors. It remains to be determined which type of enterostomy can bring more benefits to patients. This study compares the differences in the degrees of benefits for patients between ileostomy and colostomy from multiple dimensions.Materials and methodsIn accordance with the PRISMA statement, the databases such as CNKI, PubMed, Embase, and The Cochrane Library were systematically searched for Chinese and English literatures that were publicly published from 2000 to 2025. The literatures were screened according to the established inclusion and exclusion criteria, and the data were independently extracted by two researchers. The Cochrane bias risk assessment tool was used to evaluate the quality of the literatures. RevMan 5.3 was applied for statistical analysis, including heterogeneity test, calculation of p values and odds ratios (OR values), assessment of publication bias, and performance of sensitivity analysis.ResultsA total of 630 studies were initially retrieved, and finally 8 randomized controlled trials were included. The quality of the literatures varied. Most of the studies performed well in key aspects, but some had certain defects. After data combination, the final calculation showed that the odds ratio (OR) was 0.43, with a 95% confidence interval (CI) of [0.28, 0.65], and p < 0.0001. The analysis results indicated that within the 95% confidence interval, there were significant differences in the incidence rates of various complications between ileostomy and colostomy. Ileostomy had more advantages in reducing the overall complications of enterostomy.ConclusionIleostomy has more advantages than colostomy in reducing the overall complications of enterostomy surgery. This may be related to factors such as anatomical and physiological characteristics, the nature of intestinal contents, the location of the stoma, and surgical procedures. At the same time, complications can be prevented through multiple measures before, during, and after the operation. However, this study has limitations, such as differences among studies, a short follow-up period, and a relatively small number of included studies and patients.